Persuasive power concerning COVID-19 employed by Premier Imran Khan: A socio-political discourse analysis - Iqbal, Zafar; Aslam, Muhammad Zammad; Aslam, Talha; Ashraf, Rehana; Kashif, Muhammad; Nasir, Hafiz (UIN Salatiga, 2020)
The researchers investigate Pakistani Premier Imran Khan’s (IK) addresses to the nation concerning awareness about the causes, effects, precautions, and solutions of the Novel Corona Virus (COVID-19). Till the date, experts are not sure whether the vaccine will get developed or would we have to live with this as we did with HIV or Dengue. Consequently, leaders would need to address their nations, focusing specifically on precautions. The present research employs Aristotle’s persuasive and rhetorical devices, integrating them with Socio-Political Discourse Analysis (SPDA), to understand the social and political convincing style employed by the premiere. The researchers analyzed the data employing a qualitative approach. There are reliable findings to suggest that IK has used stable linguistic features to persuade the minds of the people, convincing them to follow the precautionary measures as ‘the only cure.’ The defending arguments about semi-lockdown or smart-lockdown were well-defined persuading the individuals; for instance, he suggested the smart-lockdown during his first address and faced criticism from the opposition. Later, the opposition and the world appreciated the policy of IK, the Premier of Pakistan, even being a developing country in the sight of the world. After one month of the first patient of the corona case reported in China, the policy of smart-lockdown was followed by most of the states fighting against COVID-19. Moreover, The Premier successfully persuaded the international financial organizations – IMF, World Bank, Development Banks, convincing them to waive off the pending payments of developing countries for the upcoming year.Keywords: COVID19, Persuasion, Socio-Political Discourse Analysis, Speeches, Linguistic Features